The stink bug, Andrallus spinidens (Hemiptera: Pentatomidae), a potential predator for effective biological control - Arash Zibaee; Samar Ramzi; Hassan Hoda (Journal of Plant Protection Research, 2020)
The aim of this review is to describe ecological and physiological features of Andrallus spinidens Fabricius and to discuss various possibilities of using it as an appropriate biocontrol agent in different agroecosystems. This hemipteran is a cosmopolitan predator of caterpillar pests of rice, wheat, soybean, moong, pigeon pea, maize, sugarcane and cowpea with special feeding on Chilo suppressalis Walker, Naranga aenescnes Moore, Helicoverpa armigera Hübner and Spodoptera litura Fabricius. Climate, spatial distribution of prey and type of agricultural crop are among the factors influencing the biology and spatial-temporal distribution of A. spinidens. Studies have shown random or aggregated distribution of the predatory bug with population peaks in April, July and October. The 1st instar nymphs have no feeding, the 2nd and 3rd (the first 2 days) instars are seedling feeders while they are voracious predators of caterpillars from the middle of 3rd instar to adulthood. The salivary gland consisted of two anterior-, two lateral- and two posterior lobes with major secretion of trypsin, chymotrypsin, amino- and carboxypeptidases. The alimentary canal has a four-sectioned midgut in which the third section seems to be the main place for digestive enzymes including α-amylase, trypsin, chymotrypsin, elastase cathepsins B, L and D as well as carboxy- and aminopetidases. Andrallus spinidens have shown compatibility with some insecticides and the entomopathogenic fungus, Beauveria bassiana. The predatory bug may be successfully reared in a laboratory using Galleria mellonella larvae as prey and both conservation and augmentation should be considered as biological control strategies against insect pests.